The effects of acute hydrogen peroxide exposure on respiratory cilia motility and viability - Francis,Richard (PeerJ, 2023)
COVID-19 has seen the propagation of alternative remedies to treat respiratory disease, such as nebulization of hydrogen peroxide (H2O2). As H2O2 has known cytotoxicity, it was hypothesised that H2O2 inhalation would negatively impact respiratory cilia function. To test this hypothesis, mouse tracheal samples were incubated with different H2O2 concentrations (0.1–1%) then cilia motility, cilia generated flow, and cell death was assessed 0–120 min following H2O2 treatment. 0.1–0.2% H2O2 caused immediate depression of cilia motility and complete cessation of cilia generated flow. Higher H2O2 concentrations (≥0.5%) caused immediate complete cessation of cilia motility and cilia generated flow. Cilia motility and flow was restored 30 min after 0.1% H2O2 treatment. Cilia motility and flow remained depressed 120 min after 0.2–0.5% H2O2 treatment. No recovery was seen 120 min after treatment with ≥1% H2O2. Live/dead staining revealed that H2O2 treatment caused preferential cell death of ciliated respiratory epithelia over non-ciliated epithelia, with 1% H2O2 causing 35.3 ± 7.0% of the ciliated epithelia cells to die 120 min following initial treatment. This study shows that H2O2 treatment significantly impacts respiratory cilia motility and cilia generated flow, characterised by a significant impairment in cilia motility even at low concentrations, the complete cessation of cilia motility at higher doses, and a significant cytotoxic effect on ciliated respiratory epithelial cells by promoting cell death. While this data needs further study using in vivo models, it suggests that extreme care should be taken when considering treating respiratory diseases with nebulised H2O2.
Keywords: Cilia; Respiratory epithelium; Hydrogen peroxide; Alternative medicine